Autophagy in peritoneal fibrosis - Su, Hong-yong; Yang, Jia-jie; Zou, Rong; An, Ning; Chen, Xiao-cui; Yang, Chen; Yang, Hai-juan; Yao, Cui-wei; Liu, Hua-feng (Frontiers in Physiology, 2023)
Peritoneal dialysis (PD) is a widely accepted renal replacement therapy for patients with end-stage renal disease (ESRD). Morphological and functional changes occur in the peritoneal membranes (PMs) of patients undergoing long-term PD. Peritoneal fibrosis (PF) is a common PD-related complication that ultimately leads to PM-injury and peritoneal ultrafiltration failure. Autophagy is a cellular process of “self-eating,” wherein damaged organelles, protein aggregates or pathogenic microbes are degraded to maintain intracellular environment homeostasis and cell survival. Growing evidence proves that autophagy is involved in fibrosis progression, such as renal fibrosis and hepatic fibrosis, in various organs. Multiple risk factors like high-glucose peritoneal dialysis solution (HGPDS) stimulate the activation of autophagy, which participates in PF progression, in human peritoneal mesothelial cells (HPMCs). Nevertheless, the underlying roles and mechanisms of autophagy in PF progression remain unclear. In this review, we elucidate the key roles and potential mechanisms of autophagy in PF, to offer novel perspectives on future therapy strategies for PF and their limitations.